Simultaneous cellulose hydrolysis and bio-electricity generation in a mediatorless Microbial Fuel Cell using a Bacillus flexus strain isolated from wastewater - Shankar, Naveen; Panchapakesan, Arun; Bhandari, Suhas; Ravishankar, H N (Research in Biotechnology, 2014)
The ability of electrochemically active bacteria to degrade natural wastes suggests a wide array of applications for waste management as well as electricity generation. This study reports the results of an experimentation where five bacteria were isolated from waste water and the electrochemical activity of one of them was confirmed by their use in a Microbial Fuel Cell. The bacterium was identified to be Bacillus flexus with a 99% similarity to the IFO 15715 strain using partial 16S rDNA sequencing. Phylogenetic analysis based on the BLAST results indicated close proximity to Bacillus megaterium, a known exoelectrogen.